The effect of advertising television broadcast migration on the attitude of television users - Nurhadi, Zikri Fachrul; Mujianto, Haryadi; Tajkiatunnufus, Taza (Universitas Padjadjaran, 2024)
Background: This research was motivated by ratifying the Job Creation Law, which was related to implementing television broadcasts in Indonesia, which were initially analogue to digital. This transition has implications for the progress of the digital television broadcast industry in overcoming inefficiencies in the analogue TV broadcasts that have been used so far. Purpose: This study aims to assess how advertising affects viewers’ cognitive, emotional, and conative attitudes as it transitions from analogue to digital TV broadcasts in the media. Method: The research method uses descriptive methods with a quantitative approach. Data collection techniques include distributing questionnaires and conducting literature studies. This research involved 100 respondents who were obtained using the probability sampling technique in the random sampling category. Results: The study’s findings indicate that the use of advertisements to promote the switch from analogue to digital TV broadcasts has a significant impact on the attitudes of television viewers in the Garut Regency with regard to cognition, affect, and conative thinking. These attitudes are demonstrated by the audience’s acceptance of new information or knowledge (cognitive), their feelings of trust following exposure to these advertisements (affective), and their desire to switch to digital TV broadcasts right away (conative). Conclusion: Indicators of advertising exposure through frequency, duration, and attention have a strong influence in influencing audiences, especially cognitive, affective, and conative aspects, where the information provided can provide new perceptions and knowledge for people who constantly see advertising broadcasts transitioning to digital TV broadcasts on television. Implications: The results of this research can provide understanding and insight regarding the transition to digital TV broadcasting and how important information is so that one day, television users who read the results of this research can pay attention to the advertisements shown on television to understand and implement the information they receive.